Child care costs and the employment status of married Australian mothers - Whelan, S; Rammohan, A (My University, 2006)
Using data from the HILDA (Household Income and Labour Dynamics), this paper examines the implications of child care costs on maternal employment status by distinguishing between full-time and part-time work. Our empirical approach uses an ordered probit model taking into account the endogeneity associated with both wages and child care costs. Results indicate that child care costs have a statistically insignificant effect on the decision to work either full time or part time. Moreover, the reported elasticities of part-time and full-time work with respect to child care costs are relatively low. This suggests that the significant subsidies paid to users of child care may have a limited role in increasing the labour market activity of married mothers.
Centre for Economic Policy Research, the Australian National University, Discussion Paper
Keywords: Gender; Gender -- Female; Child Care; Employment; Child Care -- Cost/affordability; Labour market; Employment and unemployment